Parkinson’s Disease: A Nanotheranostic Approach Targeting Alpha-Synuclein Aggregation - Zoey, Fong LaiGuan; Palanivel, Mathangi; Padmanabhan, Parasuraman; Gulyás, Balázs (Frontiers in Cell and Developmental Biology, 2021)
Parkinson’s Disease is one of the most common neurodegenerative disorders that is implicated in ageing populations. As numerous developed nations are experiencing progressively ageing populations today, there is a widespread increase and heightened propensity for the occurrence of Parkinson’s Disease cases. For a very long time, alpha synuclein aggregation has been considered the pivotal mechanism leading to the Parkinson’s Disease pathogenesis. Thus, early diagnostic, and therapeutic strategies targeting the misfolded alpha synuclein protein can potentially improve the prognosis of PD. With rapid advancement in nanotechnology in the last decade, effective solutions to various neurodegenerative and oncological diseases have been suggested. This review will explore the current innovations in nanotechnology that target the a-synuclein aggregation pathway, and reinstate the promise they hold as effective early diagnostic and therapeutic solutions to PD.